COX-2 inhibition: a possible role in the management of prostate cancer? - Sooriakumaran, P; Langley, SE; Laing, R; Coley, H (2007)
There is mounting evidence to support a role for cyclooxygenase-2 (COX-2) inhibitors (coxibs) in the management of prostate cancer. This review considers the current evidence base for the use of coxibs in prostate cancer as well as their adverse event profile. A systematic literature review using the search terms 'cyclooxygenase', 'COX-2', 'coxibs', 'cardiovascular risk', and 'prostate cancer' was performed using Medline. Celecoxib appears safer in terms of cardiovascular toxicity than other coxibs, and this may relate to its lower selectivity for the COX-2 enzyme. This lower selectivity also provides rationale for its putative broader anti-cancer effects, via non-COX-2-dependent pathways that affect cell cycle regulation, angiogenesis, and hypoxic modulation. There are also interacting relationships between COX-2, chronic inflammation, and prostate cancer. There is much promise for the coxibs as anti-cancer agents. The future might be to pharmacologically adapt these agents to exert their COX-2 independent mechanisms of action while minimizing their COX-2-dependent adverse cardiovascular effects.